PROTOTYPING MODEL FOR DESIGNING A DESKTOP-BASED TRADING ROBOT APPLICATION - Rahmad, Ali; Rozi, Fatchur; Rachman, Andy; Putri, Anggi Yhurinda Perdana (UTSAHA: Journal of Entrepreneurship, 2025)
The rapid development of the digital economy has stimulated increasing public awareness and literacy regarding investment and trading activities, particularly following the COVID-19 pandemic. This phenomenon has triggered the emergence of various new investment instruments, including cryptocurrency, foreign exchange, and commodity trading such as gold. To minimize trading chaos and failure resulting from emotional and psychological factors, automated trading applications known as Expert Advisors represent viable alternative solutions. This research aims to develop a desktop-based trading robot application using the prototyping model methodology. The research methodology encompassed field surveys, interviews, literature reviews, iterative application development, and comprehensive feasibility testing. The prototyping model consisted of sequential processes: initial requirement gathering, design, prototype construction, customer evaluation, review and modification, customer satisfaction assessment, development, testing, and maintenance. The developed trading robot application was successfully implemented and evaluated through the System Usability Scale (SUS), achieving an aggregate score of 88.21%, indicating excellent usability and substantial user convenience facilitation. Furthermore, the application underwent quality assessment using ISO 9126-3 framework, evaluating Functionality and Usability dimensions. The Functionality factor attained an average score of 89%, confirming that the application functions exceptionally well, while the Usability factor achieved an average score of 95%, demonstrating high usefulness. These findings validate the effectiveness of the prototyping model in developing automated trading systems that balance technical sophistication with user accessibility.